Holography Recent Advances and Applications - Rosen, Joseph (IntechOpen, 2023)
Holography of today is a broad field developed in the meeting between optics and the digital world of computers. A hologram usually contains more or different information on the observed scene than a regular image of the same scene. The development of the field has been accelerated lately due to the improvement of digital cameras, computers, light sources, and spatial light modulators. As a multidisciplinary area, holography connects experts in electro-optical engineering, image processing, and computer algorithms. More experts are needed when holography is utilized in various applications such as microscopy, industrial inspection, biomedicine, and entertainment. This book provides an overview of the world of holography from the aspect of concepts, system architectures, and applications.